PEMAHAMAN TEORI DATA WAREHOUSE BAGI MAHASISWA TAHUN AWAL JENJANG STRATA SATU BIDANG ILMU KOMPUTER - Spits Warnars, Harco Leslie Hendric; Suria, Epafras; Jeremy, Darren Kent (Jurnal Informatika, 2015)
As a Computer scientist, a computer science students should have understanding about database theory as a concept of data maintenance. Database will be needed in every single human real life computer implementation such as information systems, information technology, internet, games, artificial intelligence, robot and so on. Inevitably, the right data handling and managament will produce excellent technology implementation. Data warehouse as one of the specialization subject which is offered in computer science study program final semester, provide challenge for computer science students.A survey was conducted on 18 students of early year of computer science study program at Surya university and giving hypothesis that for those students who ever heard of a data warehouse would be interested to learn data warehouse and on other hand, students who had never heard of the data warehouse will not be interested to learn data warehouse. Therefore, it is important that delivery of the Data warehouse subject material should be understood by lecturers, so that students can well understoodwith the data warehouse.